NILAI-NILAI PENDIDIKAN KARAKTER PERSPEKTIF AL-QUR?AN SURAH LUQMAN AYAT 12-19 - Fitria, Nurin (Al Ulya: Jurnal Pendidikan Islam, 2022)
Seeing the current educational problems that prioritize written values over moral values, even though moral values are one of the most important things for the future of students. Therefore, it is necessary to strengthen character education in the current era of disruption. This study aims to provide knowledge related to the value of character education based on the Qur'an Surah Luqman Verses 12-19.This research focuses on (1) How the character values in the Qur'an Surah Luqman Verses 12-19. (2) How is the process of instilling character values in the Qur'an Surah Luqman Verses 12-19This research uses a qualitative approach with a type of text study research. Data collection is carried out by studying documents taken from the Qur'an, as-Sunnah, books and journals. The grand book of interpretation becomes the author's main reference in understanding a Verse. The data data were analyzed using inductive, deductive and comparative methods, besides that the authors also used maudhu'i or thematic methods.The results showed that: (1) the character education values contained in Surah Luqman 12-19 include character. a) Character of gratitude to God, b) Character of Faith in God, c) character of obedience and filial piety to parents, d) character of doing good e)character of worship f) social character. Meanwhile, in the Ministry of National Education in 2013 there are values of character education which can be taken in accordance with Surah Luqman Paragraphs 12-15, namely: a) religious, b) communicative, c) responsibility. Verses 16-19 are: a) religious b) honest c) dislipin, d) hard work e) independent. (2) The process of planting character values in Surah Luqman Verses 12-19 can be summed up as follows: a) first Luqman formulates the educational purpose for which is loaded in Surah Luqman which is to seek to make man an integral human being and who is rich in good character values which are sourced from the Qur'an and hadist. b) the material formulated by Luqman on the material of faith, faith and morality. Whereas the method Luqman used was by the method of advice, example, encouragement, threat or prohibition.